2020
DOI: 10.1007/s12350-018-1290-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between microvascular changes, autonomic denervation, and myocardial fibrosis in Chagas cardiomyopathy: Evaluation by MRI and SPECT imaging

Abstract: Combined myocardial analysis of the extent and location of autonomic denervation, hypoperfusion, and scarring may allow for better understanding of the pathophysiology of Chagas cardiomyopathy. Autonomic myocardial denervation may be a more sensitive marker of cardiac involvement in Chagas Disease than finding by other imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
2
19
0
13
Order By: Relevance
“…15 This study demonstrated a strong correlation between areas of denervation, hypoperfusion and fibrosis, but the areas of denervation were larger than areas of hypoperfusion or fibrosis. 15 Another study included patients with indeterminate form and cardiac form with or without systolic dysfunction and demonstrated that changes in sympathetic denervation occurred early in Chagas' disease and that they correlated with perfusion disorders and could occur before contractile changes were evident. 5 Finally, two of these studies compared the results of myocardial scintigraphy between patients with and without sustained ventricular tachycardia.…”
Section: Methodsmentioning
confidence: 55%
See 2 more Smart Citations
“…15 This study demonstrated a strong correlation between areas of denervation, hypoperfusion and fibrosis, but the areas of denervation were larger than areas of hypoperfusion or fibrosis. 15 Another study included patients with indeterminate form and cardiac form with or without systolic dysfunction and demonstrated that changes in sympathetic denervation occurred early in Chagas' disease and that they correlated with perfusion disorders and could occur before contractile changes were evident. 5 Finally, two of these studies compared the results of myocardial scintigraphy between patients with and without sustained ventricular tachycardia.…”
Section: Methodsmentioning
confidence: 55%
“…Sympathetic denervation has also been demonstrated in patients with the indetermate 5,12 and cardiac 5,14,16 forms of Chagas disease. There was a concordance between areas of denervation, hypoperfusion and fibrosis, however with areas of denervation larger than those of hypoperfusion, which characterized the "mismatch" 5,15 . The frequency of patients with sympathetic denervation and its extension gradually increased from the indeterminate form, to the cardiac form without LV dysfunction and with LV 5 systolic dysfunction.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…36 A more recent study employed image co-registration in 13 patients with CCC to investigate quantitative and topographic correlations between areas of cardiac sympathetic denervation using 123 I-MIBG-SPECT, myocardial hypoperfusion using 99m Tc-sestamibi-SPECT, and myocardial scarring using magnetic resonance imaging (MRI). 37 The results showed strong topographic agreement between areas of denervation and areas of stress-hypoperfused myocardium, corresponding to 60.8% of the denervated area. MRI showed that only 16.1% of the denervated area corresponded to areas of fibrosis.…”
Section: Myocardial Sympathetic Innervation Imaging With 123 I-mibgmentioning
confidence: 73%
“…MRI showed that only 16.1% of the denervated area corresponded to areas of fibrosis. 37 Miranda et al, 35 addressed the correlation between presence and extent of myocardial sympathetic denervation and occurrence of severe ventricular arrhythmia in CCC patients with normal or mildly reduced LVEF. 35 In this study, patients with sustained ventricular tachycardia had higher 123 I-MIBG summed defect scores than 11 patients without sustained ventricular tachycardia.…”
Section: Myocardial Sympathetic Innervation Imaging With 123 I-mibgmentioning
confidence: 99%